An Investigation on Users’ Perceptions of Open Government Data in Qatar - Rima Charbaji El-Kassem; Ali Al-Kubaisi (Human Behavior and Emerging Technologies)
This study is aimed at evaluating users’ perceptions of open government data (OGD) in Qatar, addressing disparities between the perceived performance and perceived importance of OGD, and identifying the antecedents and consequences of OGD gaps. Data collected from 1426 respondents through a questionnaire were analyzed using multiple quantitative approaches, including importance-performance analysis (IPA)–based strengths, weaknesses, opportunities, and threats (SWOT) analysis; gap analysis; factor analysis; multiple regression; and path analysis. Among 13 OGD attributes, six were identified as opportunities, five required improvement, and two were considered lower priorities. The OGD gap revealed an 82% surplus. Path analysis demonstrated that the OGD gap, combined with two other latent variables, significantly influenced users’ trust in OGD. This study prioritizes areas for improving OGD attributes, aiming to enhance users’ trust in OGD.